2016
DOI: 10.1016/j.commatsci.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Ab-initio investigation of the finite-temperatures structural, elastic, and thermodynamic properties of Ti3AlC2 and Ti3SiC2

Abstract: In this work, we calculate the structural, elastic, thermodynamic properties of Ti 3 SiC 2 and Ti 3 AlC 2 using a density functional theory (DFT) framework. The vibrational, electronic and quasi-harmonic contributions as well as an anharmonic correction to the total free energy of the system are computed and extrapolated to determine the finite-temperatures properties of the systems. Charge densities, electron localization functions (ELF), the electronic density of states (EDOS) and the vibrational density of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…However, at high temperature, E decreased slightly with increasing temperature for all solid solutions and end-members as it is illustrated in Figure 8b, without showing any deviation from the monotonic decreasing trend at BPT temperatureat around 900 o C. Comparison with DFT calculation for two end members [49] in Figure 8 shows that experimental and modeling results are in relatively good agreement, with slightly smaller decrease of predicted elastic with increasingtemperature.…”
Section: Elastic Moduli Of Ti 3 (Al 1-x Si X )C 2 Solid Solutionsmentioning
confidence: 60%
See 1 more Smart Citation
“…However, at high temperature, E decreased slightly with increasing temperature for all solid solutions and end-members as it is illustrated in Figure 8b, without showing any deviation from the monotonic decreasing trend at BPT temperatureat around 900 o C. Comparison with DFT calculation for two end members [49] in Figure 8 shows that experimental and modeling results are in relatively good agreement, with slightly smaller decrease of predicted elastic with increasingtemperature.…”
Section: Elastic Moduli Of Ti 3 (Al 1-x Si X )C 2 Solid Solutionsmentioning
confidence: 60%
“…a) The Young's modulus of Ti 3 (Al 1-x Si x )C 2 solid solutions as a function of Si content at room temperature, where calculated values are derived from DFT[30]; (b) The Young's modulus of Ti 3 (Al 1-x Si x )C 2 solid solutions as a function of temperature, where the dash line is the Young's modulus of two end members that are calculated from DFT[49].…”
mentioning
confidence: 99%
“…41 3.082 18.642 6.0487 Calc. 30 3.083 18.652 6.040 163.35 Ti 3 SiC 2 This work 3.0697 17.6864 5.7000 145.60 180.5 4.14 Exp. 41 3.075 17.734 5.7672 Calc.…”
Section: Resultsmentioning
confidence: 94%
“…Son et al . 30 have used density functional theory (DFT) to analyze the structural, elastic, and thermodynamic properties of Ti 3 SiC 2 and Ti 3 AlC 2 crystals. In order to discover the finite-temperature properties of these crystals, the vibrational, mechanical, quasi-harmonic contributions, and anharmonic adjustment to the total free energy of the systems were determined and extrapolated and the functions of electron localization, charge densities, electronic and vibrational densities have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study of electronic structure and bonding properties of Ti3AlC2, Wang and Zhou 17 reported that electrical conductivity of Ti3AlC2 decreases with increasing pressure, and over the whole pressure range, the material was found to exhibit elastic anisotropy. Furthermore many other studies were, more recently reported on the mechanical properties, and structural stabilities of Ti3SiC2 and Ti3AlC2 [18][19][20][21][22][23] since both materials exhibit excellent structural properties that are suitable for many practical applications. Synchrotron xray diffraction measurements indicate that the Ti3SiC2 and Ti3AlC2 materials as stable materials under pressure from 0 to 61 GPa at room temperature 24 .…”
Section: Introductionmentioning
confidence: 99%